Innovation Strategy and Sustainability of Micro, Small and Medium Enterprises in South East Nigeria (International Journal of Business, Economics and Management, 2020)
The current challenges and competition facing micro, small and medium enterprises in Nigeria today which is as a result of innovation has become a threat to the development of Micro, Small and Medium Enterprises. Therefore this study seeks to determine the extent to which innovation strategy can sustain MSMES in South East, Nigeria. The specific objective is to identify the extent of relationship that exists between disruptive innovation and business value contribution of MSMES in South East Nigeria. The study was guided by one research question and one hypothesis. The correlational survey design was adopted. The study was anchored on Schumpeter’s Innovation Theory (1885-1972).The population of the study was 1544 MSMES and 317 were sampled. The data used was primary data collected through structured questionnaire. The data collected was analyzed using Pearson Product Moment Correlation. The findings revealed that there is a positive relationship between disruptive innovation and business value contribution of Micro, Small and Medium Enterprises in South East Nigeria. The study recommends among others that Micro, Small and Medium Enterprises should ensure that their employees are competent so as to measure to the innovative changes in the industry.